Scribe marks at fuselage joints : initiation and propagation of fatigue cracks from mechanical defects in aluminium alloys - Cini, Andrea (Cranfield University, 2012)
Mechanical damages, like scratches, are commonly detected on the surfaces of aircraft components and structures. They can be accidentally introduced during machining or maintenance operations or be the result of wear and impacts during aircraft service. Under the action of service loads, such mechanical damage can generate fatigue cracks reducing the component fatigue life and compromising the aircraft structural integrity. The evaluation of the effect of scratches and other small mechanical defects on the structure and component fatigue lives is therefore necessary to define an inspections programme and ensure the structural safety. Conventional fatigue life prediction methods generally consider scratches tents of microns deep too shallow to appreciably affect the fatigue performances of structural components. However the discovery of the scribe marks on fuselage joints disproved that prediction. In fact several commercial airlines discovered during inspections that aircraft which have been repainted showed multiple scratches on the fuselage skin along longitudinal and circumferential joints. Those scratches, referred to scribe marks, appear to have been caused by use of sharp tools during sealant removal process prior repainting. Scratches less than 200 μm deep were capable of severely reducing the fatigue life performance under service load rendering some aircraft beyond economical repair. This thesis investigates the fatigue performances of 2024-T531 aluminium alloy sheets weakened by mechanically machined scratches. 2 mm thick clad and unclad samples were scribed at their gauge section using a diamond tipped tool. The scribing process produced very regular rounded V-shaped notches with an included angle of 60° across the sample width. Scratches from 25 μm to 185 μm deep, with 5 μm, 25 μm and 50 μm root radii were cut on the sample surfaces. Scribed sample were subsequently fatigue tested under constant amplitude tensile and bending load with a stress ratio of R=0.1 at a maximum stress of 200 MPa. Scribes were found to reduce the fatigue life of tension and bending samples up to 97% compared to that of smooth unscribed specimens. Both scribe shape and size affected the fatigue life of tensile and bending aluminium samples. The sharper and the larger the notch, the shorter the fatigue life. Post failure fractography investigations were performed on sample fracture surfaces by means of optical and scanning electron microscope. Crack nucleation sites, fracture morphology and peculiar features left during crack propagation were analysed. Finally crack propagation data under different loading conditions were obtained by striation counting performed on fracture surfaces. Multiple crack initiation occurred at scribe roots usually from inclusions, defects or weak points along the root. The number and density of crack nucleation sites appeared to be determined by the scribe; increasing for notches with larger stress concentrations. Scribe geometry did not affect the fatigue growth rate but the propagation life for cracks deeper than 50-100 μm was influenced. Cracks nucleated from scribe marks showed a typical short crack behaviour growing faster than long cracks with the same linear elastic stress intensity factor. Finite element calculations were performed on scribed samples evaluating how the presence of scribes altered the local stress and strain fields. Monotonic elastic and elastic-plastic and cyclic elastic-plastic analyses were carried out under tensile and bending loads. Local elastic-plastic stress and strain fields in the neighbourhood of different scribes were determined by the notch shape and size. According to the occurrence of mechanical similitude conditions, scribes with the same shape but different size showed similar plastic zone and stress and strain distributions. A stabilised cyclic plastic zone was developed just at the root of scribes with a ratio between the root radius and depth ρ/d≤0.2. No correlations were observed between the occurrence of a stabilised cyclic plastic zone and the sample nucleation lives defined as the number of cycles to obtain an initial crack 50 μm deep from the notch root. Traditional fatigue life prediction methods, based on the notch sensitivity factor, were not able to correctly characterise the effect of scratches few tens of microns deep on the fatigue life of 2024-T351 aluminium alloy components. An approach based on the critical distance theory was developed to characterise the total fatigue life reduction produced by the introduction of scribes relating the fatigue live to a critical stress range Δσlm. The critical stress range was capable of describing the effect of the elastic stress distribution produced by dissimilar notches on the nucleation and propagation of fatigue crack considering also the effect of the variation of the fatigue load nominal applied stress.